A transport-layer approach for improving thin-client performance in a WAN environment. (1st January 2011) - Ogawa, Yukio; Hasegawa, Go; Murata, Masayuki
The performance of thin-client systems based on TCP depends on network quality, so it becomes worse in a WAN environment; however, the effects of TCP mechanisms have not been clarified. In this paper, we first describe the download traffic of thin-client systems as a two-state model with interactive data flows in response to keystrokes and bulk data flows related to screen updates. Since users are more sensitive to the keystroke response time, our next objective is to minimise the latency of interactive data flows, especially when the network is congested. Through detailed simulation experiments, we reveal that the main delays are queuing delay in the bottleneck router and buffering delay in the server. We then enhance two TCP mechanisms: retransmission timeout calculation and SACK control, which negate the negative impacts of existing options and increase the interval between occurrences of large delays by about four times.